Gait Alterations in Two Young Siblings with Progressive Pseudorheumatoid Dysplasia - Silvia Sassi; Silvia Faccioli; Giuseppina Mariagrazia Farella; Roberto Tedeschi; Livia Garavelli; Maria Grazia Benedetti (MDPI AG, 2022)
Progressive pseudorheumatoid dysplasia (PPRD) is an autosomal recessive inherited skeletal dysplasia characterized by progressive non-inflammatory arthropathy affecting primarily the articular cartilage. Currently, little is known about the functional musculoskeletal aspects of these patients. In particular, an abnormal gait pattern has been described, without a clear hypothesis of the underlying causes in terms of muscular activity. This study presents the case of two siblings, 4 and 9 years old, a boy and a girl, respectively, suffering from PPRD at different stages of the disease. In addition to the clinical assessment, an instrumental gait analysis was performed. Swelling of the interphalangeal finger joints and fatigue were present in both cases. Gait abnormalities consisted of a relevant reduction in the ankle plantarflexion in the terminal phase of the gait cycle, associated with reduced gastrocnemius EMG activity and increased activity of the tibialis anterior, resulting in overloading at the initial peak of ground reaction forces. Gait anomalies observed were similar in both siblings with PPRD, although at different ages, and confirm walking patterns previously described in the literature. The calf muscle strength deficit and reduced activity during the stance phase of gait present in these two siblings indicate the typical absence of the propulsive phase. A stomping gait pattern, with the foot striking the ground hard on each step, was originally described. Further neurophysiological investigations are required to determine the origin of muscle weakness.